A CLINICAL PROFILE AND RISK FACTORS IN VENTRAL HERNIA PATIENTS: A RETROSPECTIVE STUDY - HARIYANI, VINAYKUMAR; PATEL, DIVYANG; RAMANI, JIGNESHKUMAR; RAIYANI, TEJAS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: About 4% of all hernia patients admitted to the ward had ventral hernias. Obesity, wound infections, malnutrition, immunosuppression, and inappropriate suture materials or incorrect suture placement were important causative factors for ventral hernia. Methods: This retrospective study was carried out among 50 patients of ventral hernias. Data were compiled in a pre-designed proforma using information from clinical notes, discharge summaries, and operation notes. This study excluded patients under the age of 18, those with femoral, inguinal, or posterior abdominal wall hernias. Results: The most common subtype of ventral hernia was incisional hernia (54.0%). The most common presenting symptom was swelling only (60.0%). The most common associated risk factor was obesity (36.0%) and constipation (26.0%). About 48.0% hernia occurred following gynecological procedures (hysterectomy - 22.0%, lower segment cesarean section - 8.0%, and tubectomy - 8.0%). Conclusion: The most common ventral hernia is the incisional hernia, which often occurs after obstetric and gynecological surgeries. Surgical site infection, obesity, and constipation increase the risk of ventral hernias.